Economic and financial crisis based on Troika's intervention and potentially avoidable hospitalizations: an ecological study in Portugal - Cristina Loureiro da Silva; João Victor Rocha; Rui Santana (BMC, 2021)
Abstract Background Hospitalisations for Ambulatory Care Sensitive Conditions (ACSC) cause harm to users and to health systems, as these events are potentially avoidable. In 2009, Portugal was hit by an economic and financial crisis and in 2011 it resorted to foreign assistance ("Memorandum of Understanding" (2011-2014)). The aim of this study was to analyse the association between the Troika intervention and hospitalisations for ACSC. Methods We analysed inpatient data of all public NHS hospitals of mainland Portugal from 2007 to 2016, and identified hospitalisations for ACSC (pneumonia, chronic obstructive pulmonary disease, hearth failure, hypertensive heart disease, urinary tract infections, diabetes), according to the AHRQ methodology. Rates of hospitalisations for ACSC, the rate of enrollment in the employment center and average monthly earnings were compared among the pre-crisis, crisis and post-crisis periods to see if there were differences. A Spearman's correlation between socioeconomic variables and hospitalisations was performed. Results Among 8,160,762 admissions, 892,759 (10.94%) were classified as ACSC hospitalizations, for which 40% corresponded to pneumonia. The rates of total hospitalisations and hospitalisations for ACSC increased between 2007 and 2016, with the central and northern regions of the country presenting the highest rates. No correlations between socioeconomic variables and hospitalisation rates were found. Conclusions During the period of economic and financial crisis based on Troika's intervention, there was an increase in potentially preventable hospitalisations in Portugal, with disparities between the municipalities. The high use of resources from ACSC hospitalisations and the consequences of the measures taken during the crisis are factors that health management must take into account.